Pengaruh Lingkungan Terhadap Prestasi Belajar Matematika Siswa Kelas X Di SMA Plus Ibadurrahman: The Influence of the Environment on Mathematics Learning Achievement of Class X Students at SMA Plus Ibadurrahman - ahmad fahrudin; Hapsari Widayani (Institute of Advanced Knowledge and Science, 2023)
The purpose of this study is to ascertain if the learning environment at SMA Plus Ibadurrahman has an impact on the Mathematic’s learning achievement of class X students. by employing route analysis in quantitative research techniques. Simple linear regression analysis, correlation coefficient analysis, and coefficient of determination analysis are the data analysis methods that are employed. The value of the basic linear regression equation, Y = 45.129 + 0.35X, is shown by the research's findings. There is a substantial association between learning accomplishment and the learning environment, as indicated by the correlation coefficient value of rxy = 0.728. KD achieved is 53%. It can be inferred that, among the tenth grade students at SMA Plus Ibadurrahman, 53% of their mathematic learning accomplishment is attributed to their learning environment, and 47% is determined by other factors not included in this study. Results of the hypothesis test and computations are achieved if tcount > ttable (8.822 > 1.994). The findings indicate that the learning environment (variable X) and learning achievement (variable Y) of class X students at SMA Plus Ibadurrahman have a positive and significant relationship.